Uma análise marxiana do direito ao trabalho : da normatização à execução no Brasil - Damascena, Monique Bronzoni (2017)
The labor is incorporated into the market society as a manner to accumulate wealth and, accordingly, all the social structure is oriented to the social relationships which arise from the capitalist system. As a consequence, the right to work in Brazil has been regulated by the mutual interaction between such social relation and the social structure of the economic system. Attempting to explain this social phenomenon, this thesis aims to realize a Marxian analysis on it, utilizing to do so the dialectic-critic method. After bringing the essence of the labor into the picture, the study was able to explain how the labor constitutes itself as wealth to the economic system, its regulation as a social right, and its execution through social programs focused on the productive inclusion. The performed analysis was based on quantitative-qualitative bibliography research, which included several academic works on the subject. From such analysis, some conclusions can be inferred: a) the essence of the labor was kept apart from the social being, thereby benefiting the values of the abstract labor but imposing to the human personality development a considerable disadvantage. b) the type of labor which is capable of generating wealth directly is the productive labor, whereas the one which generates it indirectly is the unproductive labor. c) the right to work, considering its wider sense, is partially guaranteed. d) the guarantee of having labor as a social right does not impose itself on the right of accumulate wealth. e) the right to work regulation in Brazil is mainly determined by relations involving paid employment (labor right). f) the right of work provided by the state offers minimal conditions for labor, subsistence, and consumption. g) the actions related to the right of work, at the collective level and aiming social promotion, are guaranteed in laws and government programs oriented to professional qualification. h) the actions of productive inclusion are not sufficient to guarantee minimal conditions of subsistence and they do not ensure the reduction of social and income inequality. After facing such conclusions, this work suggests as resistive measures to this context, the understanding of the limits of the state, the government, and the right to work. These limits point out new frontiers that might be explored by revolutionary processes within the market society, which are typically presented as illegitimate, illegal, or even unfair.